Signs of change: Evidence on women’s time use, identity, and subjective well-being in rural Bangladesh - Seymour, Greg; Floro, Maria S. (Africa Centre for Gender, Social Research and Impact Assessment, 2021)
We develop an analytical framework based on the work of Akerlof and Kranton (2000) and use it to examine how identity – proxied by agreement with statements reflecting patriarchal notions of gender roles – affects the trade-off between the time women spend on household and care work and their subjective well-being. Analyzing household survey data from rural Bangladesh, we find that longer hours spent on household work are associated with lower levels of subjective well-being among women who hold egalitarian notions of gender roles, while the reverse is true for women who hold patriarchal notions of gender roles. Importantly, this pattern holds only when women strongly identify with patriarchal or egalitarian notions of gender roles. These findings provide insights into how social expectations govern gender roles and, specifically, how gender inequalities persist, at least in part, due to men’s and women’s internalization of traditional gender norms.